Toothless tiger with claws? Financial stability communication, expectations, and risk-taking - Johannes Beutel; Norbert Metiu; Valentin Stockerl (Deutsche Bundesbank, 2021)
We study the effects of central bank communication about financial stability on individuals' expectations and risk-taking. Using a randomized information experiment, we show that communication causally affects individuals' beliefs and investment behavior, consistent with an expectations channel of financial stability communication. Individuals receiving a warning from the central bank expect a higher probability of a financial crisis and reduce their demand for risky assets. This reduction is driven by downward revisions in individuals' expected Sharpe ratios due to lower expected returns and higher perceived downside risks. In addition, these individuals deposit a smaller fraction of their savings at riskier banks.
Keywords: C11; D12; D83; D91; E58; G11; 330; central bank communication; financial stability; stock market expectations; randomized information experiment